Supramolecular Adhesives to Hard Surfaces: Adhesion Between Host Hydrogels and Guest Glass Substrates Through Molecular Recognition. Issue 19 (27th August 2014) - Takashima, Yoshinori; Sahara, Taiga; Sekine, Tomoko; Kakuta, Takahiro; Nakahata, Masaki; Otsubo, Miyuki; Kobayashi, Yuichiro; Harada, Akira
<x xml:space="preserve">Abstract</x> Supramolecular materials based on host–guest interactions should exhibit high selectivity and external stimuli‐responsiveness. Among various stimuli, redox and photo stimuli are useful for its wide application. An external stimuli‐responsive adhesive system between CD host‐gels (CD gels) and guest molecules modified glass substrates (guest Sub) is focused. Here, the selective adhesion between host gels and guest substrates where adhesion depends on molecular complementarity is reported. Initially, it is thought that adhesion of a gel material onto a hard material might be difficult unless many guest molecules modified linear polymers immobilize on the surface of hard materials. However, reversible adhesion of the CD gels is observed by dissociating and re‐forming inclusion complex in response to redox and photo stimuli. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>